MVK, induced by Kras, represses cGAS-Sting signalling in lung adenocarcinoma - Changsheng Zhou; Jia Liu; Xudong Hu; Lu Lu; Juan Hou; Jian Wang; Liqun Jiang; Shuangshuang Huang; Yu Lin; Luyao Liu; Lingling Cui; Yiqian Liu; et al. (European Journal of Medical Research)
Abstract Cholesterol metabolism is abnormally active in tumour cells. Metabolic enzymes related to cholesterol metabolism are upregulated in tumours, but their nonmetabolic functions remain unclear. We found that MVK (mevalonate kinase) is upregulated in lung adenocarcinoma tissues vs. normal tissues and that its expression can be induced by constitutively activated Kras. By investigating the molecular mechanisms involved, we discovered that MVK interacts with TBK1, inhibiting TBK1 phosphorylation and thereby suppressing cGAS-Sting signalling. In addition, we found a negative correlation between MVK expression and CD8+ T-cell infiltration via a public database analysis. In summary, our study demonstrates the importance of the nonmetabolic function of MVK in modifying the immunological milieu and provides new targets for lung adenocarcinoma therapy.